How Taoism addresses unbalanced lives of urban female : see things differently - Lam, Nu Lien Minh (2012)
Born, educated and grown in developing countries that are still faithful to tradition and cultural heritage, young Asian women encounter inevitable tensions between tradition and modern lifestyles that makes her loose harmony and balance in her daily life.